Implementation Status of the Citizen's Charter in District Administrative Office Morang (The Journal of Knowledge and Innovation, 2024)
The Citizen’s Charter is a chart of commitment to the public or service recipients of the organization detailing the services provided by that office and the quality of those services. This article aims to identify the awareness level of people & service delivery of District administrative office, Morang towards citizen. Purposive sampling was applied for selecting service provider and service receivers. Qualitative method i.e. interview methods was used with the service provider. Moreover observation method was also applied to dig out the reality of the service. Quantitative methods i.e. questionnaire with the service receiver was also employed. The citizen’s charter was available in the premises of district administrative office Morang. Public awareness of the citizens and service quality were good. Most of the service receivers had good knowledge about the charter. Few respondents had little knowledge and were unaware about citizen charter. The service delivery was good in terms of quality and promptness of the service and management of citizen charter in the office premises. However due to some political-administrative and personal circumstances, some of the irrational results were found. There is the systematic use of the citizen charter in the DAO. The level of knowledge of the people about it and the quality of the service delivery of the system is good but there are some shortcomings such as low awareness among uneducated people. Therefore, is essential to increase public awareness about citizen charter.